Teaching Strategies Preferences of Male and Female English Teacher in SMPN 4 Singaraja - Juliani, Made Dian; Artini, Luh Putu; Agustini, Dewa Ayu Eka (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2025)
The aim of this research is to obtain a profile of the most frequently used teaching strategies most frequently used by teachers based on the perspectives of two different genders; male and female. The strategies being observed were focused on the teaching strategies recommended by the new curriculum; Merdeka Curriculum. Data collection were done within 3 different instruments; teaching strategy checklist, observation checklist, and in-depth interview guide. This research involved one male teacher and one female teacher, conducted in SMPN 4 Singaraja. The findings showed that male teacher is tend to applied Deductive Application of Rules, a strategy part of Grammar Translation Method. On the other hand, female teacher sowed preferences in Guided Discovery strategy. Both of the teacher stated that the reason underlying their preferences is because of the material taught on the day and the students’ characteristics. This research also found that both of the teacher frequently applied social affective strategy, where teacher maintain students’ learning process by emphasizing the socio-emotional aspects. The findings can inform teacher training programs to tailor strategy selection based on both curriculum demands and the diverse instructional preferences of educators.